Psikoedukasi Pola Asuh Pada Ibu-ibu di Wilayah Puskesmas Keputih, Surabaya: Psychoeducation of Parenting To Mothers at Puskesmas Keputih, Surabaya - Yolanda Candra Arintina (Lembaga Penelitian dan Pengabdian Masyarakat UNJ dan Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2020)
The psychoeducation program regarding parenting style for mothers was conducted as a part of a psychological intervention. This intervention aims to increase the understandingof parenting among mothers in Kenanga Maternal and Child Health Service in Puskesmas Keputih, Surabaya area, by giving Psychoeducation of Parenting. Fourteen mothers were included as the participants in this intervention by using purposive sampling technique. The pretest and posttest questionnaire were given to the subjects to measure the understanding of parenting before and after the intervention. The finding showed that the psychoeducation as the intervention increase the understanding of parenting among mothers in Kenanga Maternal and Child Health Service in Puskesmas Keputih, Surabaya (Asymp. Sig (2-tailed)0.001 < 0.05). This study led to the suggestion of conducting the intervention in the prospective time with the greater area